Pengaruh Penerapan Pendekatan Socio Scientific Issues Terhadap Kemampuan Literasi Sains Siswa Pada Materi Minyak Bumi - Afrilya, Nur’Aida; Afrianis, Neti; Nurhadi, Nurhadi (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
Science literacy ability was one of abilities that should be owned by students, and this ability was on low category in Indonesia. It needed attention to be developed because of the successful indicators of chemistry learning process. This research aimed at knowing the effect of implementing Socio Scientific Issues (SSI) approach toward student science literacy ability on Crude Oil lesson at the eleventh grade of MIPA of State Senior High School 5 Pekanbaru. It was a quasi-experimenta research with pretest and posttest design. The subjects of this research werethe eleventhgrade students of MIPA in the Academic Year of 2019/2020. Simple random sampling technique was used in this research, and it was obtained two sample classes—the eleventh-grade students of MIPA 2 (experimental group) and 3 (control group). The data of this research were collected through observation, preliminary data test that was homogeneity test, and final data tests that were pretest and posttest. N-gain and paired sample t-test with SPSS 21 were used to know the effect of implementing SSI approach in increasing student science literacy ability. The obtained score of n-gain showed that there was a significant increase of student science literacy ability, it was on high category for the eleventh-grade students of MIPA 2 and it was on medium category for the students of MIPA 3. The results of analyzing the preliminary and final data showed that the score of -tobserved was -22.491, -ttable was -2.0301, and +ttable was 2.0301 at 5% significant level. The score of - observed was lower than -ttable, and tobserved was higher than ttable, so H0 was rejected and Ha was accepted. It showed that there was aneffect of implementing SSI approach toward student science literacy ability on Crude Oil lesson at the eleventh grade of MIPA of State Senior High School 5 Pekanbaru. Keywords: Socio Scientific Issues (SSI), Science Literacy, Crude Oil.